Predicting Role of the Appendicitis Inflammatory Response Score in Diagnosis and Risk Stratification of Acute Appendicitis among Adult Patients (IAHS Medical Journal, 2023)
Background: Appendicitis is a global disease. Understanding the global evolution of appendicitis in highly industrialized countries and in newly industrialized countries is necessary for planning healthcare resource utilization. Scoring systems have been designed to aid in the clinical assessment of patients with acute appendicitis. The recently introduced Appendicitis Inflammatory Response (AIR) score was designed to overcome these drawbacks. This simple clinical score can correctly classify the majority of patients with suspected appendicitis. To evaluate the AIR score on patients with suspicion of acute appendicitis and its risk stratification and assess the sensitivity and specificity of the AIR score.Materials and methods: This descriptive of observational study was carried out in the Department of Surgery, Chittagong Medical College Hospital, Chattogram from 21st March to 20th September 2017. Total 100 cases of appendicitis patients were selected after careful history taking, thorough general and local examination and appropriate investigations fulfilling inclusion and exclusion criteria.Results: The present study of 100 selected cases reveals that maximum number of patients (54.0%) were between 15-25 years age group, mean age of appendicitis was 24.5±8.9 years. The sensitivity and Specificity of the Appendicitis Inflammatory Response Score (AIR score) in diagnosis and risk stratification of acute appendicitis was 85.2% and 96.9% respectively. Similarly, the positive predictive value and accuracy rate for the same is 93.5 % and 93.0% respectively.Conclusion: Through associating easily applicable clinical criteria and two simple laboratory tests AIR score help in diagnosis and risk stratification of suspected appendicitis and could guide decision-making to reduce admissions, optimize utility of diagnostic imaging and prevent negative explorations.IAHS Medical Journal Vol 5(2), Dec 2022; 46-51